Using the teaching interaction procedure to train interventionists to implement the Cool versus Not CoolTM procedure. (21st August 2020) - Ferguson, Julia L.; Milne, Christine M.; Cihon, Joseph H.; Leaf, Justin B.; McEachin, John; Leaf, Ronald
Abstract: The teaching interaction procedure is a behavior analytic procedure that has been used to target the development of social skills. The teaching interaction procedure consists of labeling the target skill, providing a meaningful rationale, describing the steps of the target skill, modeling the skill, role‐play, and providing feedback throughout the interaction. Although the teaching interaction procedure has been used to teach a variety of social skills for individuals diagnosed with autism spectrum disorder (ASD), it has only been used to train staff in two studies. The purpose of this study was to evaluate the use of the teaching interaction procedure to teach three interventionists to implement the Cool versus Not Cool™ procedure to target the development of social skills for children diagnosed with ASD. The results of a multiple baseline design demonstrated that the teaching interaction procedure was effective for all three interventionists. Results of the child participants' skill acquisition are also provided.